Influence of citrate and EDTA anticoagulants on plasma malondialdehyde concentrations estimated by high-performance liquid chromatography - Suttnar, J; Másová, L; Dyr, J E (Journal of chromatography. B, Biomedical sciences and applications, 2001)
Estimation of lipid peroxidation through MDA formation measured by assaying thiobarbituric acid (TBA) reactive products separated by HPLC remains the method of choice to study the development of oxidative stress in blood plasma. In this report we describe the influence of citrate and EDTA anticoagulants used for blood collection on estimation of MDA concentrations using HPLC analysis of MDA-TBA adducts. We analyzed a group of 40 blood donors (21 men and 19 women), median age 27 years, range 19-48 years. The mean MDA concentration in citrate plasma was 1.43+/-0.51 micromol/l (range: 0.61-2.57 micromol/l) and in EDTA plasma 0.36+/-0.10 micromol/l (range: 0.13-0.63 micromol/l). There was a significant difference in MDA mean concentration that we attribute to different antioxidant properties of anticoagulants used for blood collection. Consistency in the choice of anticoagulant is clearly extremely important.
Keywords: Oxidative Stress; oxidační stres; Humans; Malondialdehyde; lidé středního věku; Female; dospělí; kyselina citronová; lidé; odběr vzorku krve; Adult; Edetic Acid; ženské pohlaví; Male; kalibrace; Middle Aged; thiobarbituráty; Citric Acid; Thiobarbiturates; mužské pohlaví; EDTA; antikoagulancia; malondialdehyd; Anticoagulants; Calibration; Blood Specimen Collection